(untitled) (Proceedings of Faculty of Civil Engineering, 2019)
The paper presents an overview of the historic development of tourism in Rovinj, Croatia. The development of Monte Mulini area is analysed as particularly interesting from the aspect of recent hotel construction in Croatia. On the relatively small area near the edge of forest park Zlatni Rt, in last ten years three highly categorised hotels were built on the area of existing hotel buildings, and the hotel Eden, designed by architects Bartolić and Begović, has been reconstructed. Urban and architectural characteristics of the area are analysed, as well as new construction and reconstruction characteristics of existing hotels.